Case Report: Neonatal nephropathy with polycystic appearance in child harboring WT1 variant - Nguyen, Tuyen Thi Thanh; Tran, Quynh Thuy Huong; Nguyen, Huong Thi Thanh; Pham, Trang Quynh Mai; Tran, Doan; Fukui, Kenji; Tsukaguchi, Hiroyasu (Frontiers in Pediatrics, 2025)
BackgroundMutations of the Wilms tumor suppressor-1 gene (WT1) cause a WT1-related nephropathy characterized by a triad of glomerulopathy, defective genital development, and Wilms or gonadal tumor. WT1 mutations affecting the second to third zinc finger motifs (residue 428–511) often lead to infantile-onset glomerulopathy that progresses rapidly to end-stage renal failure by the age of 2.5 years. Most of these cases have been reported as Denys–Drash syndrome (DDS). We report a patient harboring a WT1 p.Arg467Gln variant who developed a severe neonatal-onset renal failure since birth, with an unusual cystic pattern of kidney enlargement on ultrasound.Case presentationA 22-day-old neonate manifested acute anuric renal failure shortly after birth. Renal ultrasound revealed moderately enlarged, bilaterally hyperechoic kidneys (+2.0 to +3.0 SD), the appearance of which resembled that of polycystic kidney disease. The patient showed normal male external genitalia development except for undescended testes. There were no abnormalities in the hepatobiliary duct systems or lungs. The occurrence of the same cystic kidney disorder in the elder sibling born to healthy parents suggests germline mosaicism. He died from multiorgan failure on postnatal day 47.Genetic resultsThe next-generation sequencing (NGS) screening panel analysis of 4,503 known disease genes revealed a heterozygous pathogenic WT1 p.Arg467Gln variant, which has been reported elsewhere in children formerly categorized under the DDS subtype. The Arg467 residue is the most frequent site of mutations in DDS and is predicted to hinder the binding of the third zinc finger to DNA. Additionally, a heterozygous COL4A4 p.Gly864Val missense variant of uncertain significance (VUS) was detected. Genome-wide copy number analysis did not detect any structural abnormalities.ConclusionOur observation highlights two aspects of the WT1 p.Arg467Gln variant in WT1-related nephropathy: (1) The p.Arg467Gln variant causes severe neonatal-onset nephropathy likely through a potent dominant-negative inhibition, and (2) it may manifest a cystic/dysplastic renal phenotype in the presence of coexisting cytogenic modifiers. Future studies are necessary to assess the relevance of the COL4A4 variant in cystic disease and to explore hidden modifier genes through deep sequencing.